A vertical and cross-linked Ni(OH)2 network on cellulose-fiber covered with graphene as a binder-free electrode for advanced asymmetric supercapacitors1. Issue 37 (7th October 2015) - Zhang, Lin-Lin; Li, Huan-Huan; Fan, Chao-Ying; Wang, Kang; Wu, Xing-Long; Sun, Hai-Zhu; Zhang, Jing-Ping
<x xml:space="preserve">Abstract</x> A vertical and cross-linked Ni(OH)2 network on cellulose-fiber covered with graphene as a binder-free electrode for asymmetric supercapacitors exhibits excellent electrochemical performance.